Effects of silicate modulus and GBFS content on shrinkage of alkali-activated steel slag cementitious material - Jianwei Sun; Yuehao Guo; Yan Meng; Ruiquan Jia; Jiajie Zhou; Hongyuan Gao; Jie Liu (Journal of CO2 Utilization)
Alkali-activated steel slag material (ASSM), a sustainable and environmentally-friendly construction material due to its lower carbon footprint. faces challenges, particularly in terms of high shrinkage. This study investigated the relationship between autogenous shrinkage, drying shrinkage, the type and content of hydration products, and pore structure of ASSM. The effects of different silicate moduli of water glass (1.5 and 2.0) and GBFS contents (10 % and 20 %) on the properties of ASSM were evaluated with a constant alkali concentration of 4 %. The results indicate that both the silicate modulus and GBFS content significantly impact the shrinkage behavior of ASSM. Decreasing the silicate modulus and increasing the GBFS content effectively reduce both autogenous and drying shrinkages. Notably, autogenous shrinkage is reduced more significantly with an increase in GBFS content at a low modulus, while drying shrinkage is reduced more noticeably under high modulus condition. The established shrinkage models can effectively predict autogenous and drying shrinkages of ASSM. The trend of drying shrinkage in ASSM corresponds to changes in the pore structure, whereas the varying trends in autogenous shrinkage may be attributed to the formation of gel products. Increasing the silicate modulus and GBFS content does not alter the types of hydration products. An increase in the silicate modulus and GBFS content has minimal effect on the hydration degree of ASSM. By increasing both the silicate modulus and GBFS content, the pore structure of the hardened paste can be refined.